Pengaruh Isu Kampanye terhadap Preferensi Pemilih Milenial pada Pemilu Tahun 2019 di Sumatera Barat - Heru Permana Putra (Universitas Indo Global Mandiri, 2023)
This study discusses the influence of campaign issues on the preferences of the Millennial Generation in the 2019 general election. This research aims to develop a verification study, a descriptive study, and an exploration of several theories and concepts of Voting Behavior. Second, the study aims to analyze various factors influencing millennial voter preferences for a political party, legislative candidate, and presidential candidate in the 2019 election. The approach in this study uses a quantitative approach with a survey research design. While the survey research design is limited to research in which data is collected from a sample of the population to represent the population. It can be concluded that survey research takes a sample from one population and uses a questionnaire as the primary data collection tool. This research belongs to the type of explanatory research, Sig. (2-sided) 0.05, then there is a significant relationship between campaign issues and voting behavior. If the Asymp value. Sig. (2-sided) 0.05, there is no significant relationship between campaign issues and voting behavior. Asymp Value. Sig. (2-sided) 0.000 0.05, it can be concluded that there is a significant relationship between campaign issues and voting behavior. It was concluded that there is a significant relationship between campaign issues and voting behavior. It also means that the issues in the campaign correlate with voting behavior.